Smoking x Ginecological Conditions – a cross-section study (Research, Society and Development, 2020)
The aim of the study was to investigate the relationship between smoking and gynecological changes and reproductive health in users of a health unit. This is an analytical and exploratory study, carried out from a bank prepared in a previous study, in which the data were collected in a Family Health Unit in Salvador - BA. The study estimated the relationship between cigarette use and women's gynecological health. 150 women participated, most of them self-declared black and aged 38 years or less, low income and own home. Regarding the use of any contraceptive method, 76.92% of the women interviewed did not smoke or used any contraceptive method, and 23.47% of those who smoked, used some contraceptive method. Among women who did not smoke, 78.79% used hormonal contraceptives. Regarding the gynecological conditions of women who smoked, 19.28% had vaginal discharge, with the highest prevalence being secretion with a bullous appearance (28.36%), 17.65% had a precursor lesion for cervical cancer and 18.18% Cândida sp. As for the presentation of Supracytoplasmic Bacilli, it was found in 26.47%. There was little association between smoking and gynecological disorders, however, the main findings signaled a higher frequency of gynecological infections in women who smoke. It is necessary to discuss smoking and its repercussions on health that may compromise quality and duration of life, in order to prevent risks and injuries, reduce damage and promote health.